Carcass and meat quality characteristics of Romney and three-quarter Wiltshire lambs : a thesis presented in partial fulfilment of the requirements for the degree of Master of Science in Animal Science at Massey University, Palmerston North, New Zealand - Rawidech, Rawisara (Massey University, 2024)
Self-shedding sheep breeds, like the Wiltshire, have been introduced into meat production systems in New Zealand to reduce costs such as shearing and crutching. However, there is limited information on the meat performance of Wiltshire-cross lambs. Therefore, this study aimed to assess carcass and meat quality attributes of Romney and ¾ Wiltshire lambs. Data were collected from Romney (n=11) and ¾ Wiltshire (n=12) ram lambs, managed and fed on pasture under the same conditions, and sent to slaughter, as one group when all lambs reached a minimum of 42 kg liveweight. Final on-farm liveweight, hot carcass weight and dressing-out percentage were obtained on the day of slaughter. Muscle and dissectible fat percentages, muscle-to-bone ratios for whole leg and femur, muscularity, and femur bone morphology were obtained from leg dissections. Objective meat quality assessments were conducted on a sample of the Longissimus lumborum muscle to obtain pH, colour, water-holding capacity, shear force value, intramuscular fat percentage and fatty acid composition. The start and, final on-farm liveweights and hot carcass weights of the ¾ Wiltshire lambs were heavier than Romney lambs (P<0.05). Muscle and intramuscular fat percentages, muscle-to-bone ratios and muscularity did not differ between treatments (P>0.05). The ¾ Wiltshire lambs had lower dissectible fat percentages and greater muscle weights surrounding the femur compared with the Romney lambs (P<0.05). The ¾ Wiltshire lambs had greater femur bone length, total bone content, density, cortical bone content and thickness, and bone stress strain index compared with the Romney lambs (P<0.05). However, total bone area, cortical bone density, and periosteal and endosteal circumferences of both treatments were the same (P>0.05). There was no difference between the two genetic differences in meat colour, water-holding capacity, shear force and fatty acid profile (P>0.05). The results suggest that the ¾ Wiltshire lambs produce carcass and meat quality characteristics that are comparable to Romney lambs when slaughtered at a similar age. Therefore, the use ¾ Wiltshire lambs will not negatively affect meat yield and meat quality and will not be disadvantaged when used in lamb meat production systems.
Keywords: 300301 Animal growth and development